Clinical profile and management outcomes of paediatric undescended testes in a Nigerian tertiary hospital: An 11-year review - Ituen MA; Akpanudo EI; Eyo AE; Emmanuel EM (Ibom Medical Journal)
Context: Undescended testis (UDT) is a common urogenital abnormality in male children, and early intervention is imperative to prevent impaired spermatogenesis or malignant transformation.